2023
DOI: 10.1097/lvt.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation with uncontrolled versus controlled DCD donors using normothermic regional perfusion and ex-situ machine perfusion

Abstract: Background: In Italy, 20 minutes of continuous, flat-line electrocardiogram are required for death declaration, which significantly increase the risks of DCD LT. Despite prolonged warm ischemia time, Italian centers reported good outcomes in controlled DCD (cDCD) LT by combining normothermic regional and end-ischemic machine perfusion. However, data on uncontrolled DCD (uDCD) LT performed by this approach are lacking. Patients and Methods: This was a multicenter, retrospective study performed at three large vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Against this background, the study by Ghinolfi et al 7 is timely. The authors examined the use of NRP combined with ex situ MP and compared the results achieved in cDCD with uDCD.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Against this background, the study by Ghinolfi et al 7 is timely. The authors examined the use of NRP combined with ex situ MP and compared the results achieved in cDCD with uDCD.…”
mentioning
confidence: 97%
“…[6] However, the combination of NRP and ex situ MP has not been previously explored in the setting of uDCD liver transplantation. [6] Against this background, the study by Ghinolfi et al [7] is timely. The authors examined the use of NRP combined with ex situ MP and compared the results achieved in cDCD with uDCD.…”
mentioning
confidence: 98%
“…The most substantial issue in the discussion of nonstandard donor organ usage is the rapid adoption in many centers of machine perfusion technology which allows nonstandard donor organs to be sustained for increased amounts of time and for organs to also be procured from much farther away than previously. [8] The centers noted to have the highest donation after cardiac death usage-Mayo Clinic Arizona (AZMC), Jackson Memorial-Miami (FLJM), Cleveland Clinic (OHCC), and Ohio State University (OHOU)-have all participated in published case series or publicly advertise their use of machine perfusion pumps. [9][10][11] Public sharing in the United Network of Organ Sharing of nonstandard donor usage, if it affects patient selection of transplant centers, may drive higher adoption of this technology.…”
mentioning
confidence: 99%
“…In the Tuscany Region [4] the uDCD program has been implemented since 1 June 2016 and, to date, two lungs, 22 livers and 66 kidneys have been transplanted from uDCDs with acceptable outcomes. In a multicenter, retrospective study performed at 3 large-volume centers comparing clinical outcomes of 40 uncontrolled versus 59 controlled DCD liver transplantations [7], one-year graft survival was lower in uDCD (75% vs. 90%, P = 0.007) but became comparable when non-liver-related graft losses were treated as censors (77% vs. 90%, P = 0.100). The Authors concluded that liver transplantation from uDCD was feasible by the sequential use of normothermic regional perfusion and end-ischemic machine perfusion.…”
mentioning
confidence: 99%